Biodiversity Assessments In Baseline And Monitoring Of Mining Projects - Introduction - J. Ugarte-Núñez (Society for Mining, Metallurgy & Exploration, 2011)
Biodiversity assessments that are developed in different stages of a mining project, have different objectives that define the methodology to be used in each of these stages. In this way, we define two stages of a project: 1) the time at which assesses the state of biodiversity or biological components, before any intervention in the project area, previously defining the area of direct influence and indirect influence of the project for each biological group to be evaluated and 2) the time when certain groups or biological, are monitored during the developmental stages of the project with you to obtain information about the level impact they may have, for project activities. It discusses the methodological differences that must be used in both biodiversity assessments: to develop biological baselines and in those assessments aimed at monitoring different components of biodiversity.